Justification of the usury contract in the law of the Republic of Serbia: Advantages and disadvantages - Tanja Praštalo (Economic Themes, 2020)
A usury contract is a null and void contract whereby someone, using the condition of another's misfortune or material hardship, lack of experience, recklessness, or dependency, obtains for himself or for a third party a benefit that is clearly disproportionate to what he or she has given or done in return or committed to give or do. The usury contract violates one of the basic principles of the law of obligations, which is the principle of equality of obligations, in other words, the equality of the value of mutual benefits of the contracting parties. Although the legal definition of the usury contracts (Law on Contracts and Torts, Article 141, paragraph 1) is comprehensive enough, it is not easy for the courts to decide whether one contract is usury or not, i.e. null and void. The subject of this paper is the analysis of the usury contracts through the current case law in the context of the justification of the existence of this institute in the legislation of Serbia, having in mind the division of opinions, and because as much as a party using a person's difficult material situation is presented in a negative context, the contract of this type is nonetheless a product of the willing action of both parties. The topic of this paper is very sensitive and requires a reasoned methodological approach and analysis. The aim of the paper is also to encourage the affected party in the usury contract to enter into litigation to protect their rights.
Keywords: K11; 330; usury contract; case law; justification of the usury contract inthe legislation of the Republic of Serbia; advantages and disadvantages ofthe usury contract; abuse of the usury contract; overcoming usury contractshortcomings